I’m kind of agnostic’: Belief discourse by second-generation migrants at the Tamil Saiva Temple - Perera, Niru (John Benjamins Publishing Company, 2020)
Transplanting non-Western religions to Western nations results in firstgeneration migrant attempts to transmit faith in vastly different contexts. Especially as adolescents, second-generation migrants tackle mediating their personal religious beliefs in a society with diverse religions and ideologies as well as negotiating membership of their ethnoreligious community. This paper draws from an ethnography in a Tamil Hindu temple in Australia. I present Sri Lankan teenage migrants’ discourse from their faith classroom to elucidate processes of belief positioning. In working out their emergent, and provisional, faith identities the students deploy mainly Tamil and English linguistic features in their belief narratives. Flexible languaging complements their “syncretic acts” - the practice of drawing on diverse ideologies and experiences (outside the boundaries of a particular religion) to form personalized beliefs. Translanguaging thus facilitates the expression of circumspect, nuanced and non-traditional interpretations of their heritage religion. Understanding such processes of belief positioning can help societies and institutions to work towards migrant youth inclusion.